A method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black

By using two-dimensional titanium carbide-acetylene black modified interface layer in all solid state lithium-ion batteries, the problems of poor interface modification of polymer electrolyte and lithium dendrites are solved, and the cycle stability and safety of the battery are improved, so as to achieve More uniform lithium ion deposition and higher conductivity.

CN113851705BActive Publication Date: 2024-12-27HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202111137698.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-27
Publication Date
2024-12-27
Estimated Expiration
2041-09-27

AI Technical Summary

Technical Problem

The polymer electrolyte interface modification and unstable in all-solid-state lithium-ion batteries lead to piercing the separator, causing the potential for short circuit and fire of the battery, and the low ion conductivity of the room temperature, affecting the battery performance.

Method used

The two-dimensional titanium carbide-acetylene black mixture is uniformly stirred with the polymer electrolyte precursor, and the modified coating is prepared by scraping coating to form a modified interface layer with strong conductivity and large polarization effect to ensure uniform deposition of lithium ions and reduce Interface impedance inhibits the formation of lithium dendrites.

Benefits of technology

It improves the charge/discharge specific capacity and cycle stability of all solid-state lithium-ion batteries, reduces the interface impedance, prevents lithium dendrites from punctured through the separator, and enhances the safety and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113851705B_ABST
    Figure CN113851705B_ABST
Patent Text Reader

Abstract

A method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black is used to solve the problem of large interface impedance between the polymer electrolyte and the positive electrode and unstable solid electrolyte interface film. The specific steps are: acetylene black and two-dimensional titanium carbide are evenly mixed in a mass ratio of 1:1, an electrolyte precursor slurry with a mass ratio of 5:2 to the above-mentioned solid is added to obtain an interface modification slurry, a 50 μm thick modification layer is applied on the electrolyte by a scraping method, and an electrolyte film with an interface modification layer is dried at 100°C. In the present invention, two-dimensional titanium carbide-acetylene black is used as a polymer electrolyte modification layer, and the electrolyte interface is improved by coating. The present invention effectively reduces the bulk impedance and interface impedance of the polymer electrolyte, forms a stable solid electrolyte interface layer between the polymer electrolyte and the positive electrode, prevents the formation of lithium dendrites from affecting battery performance, and improves the charge / discharge specific capacity and capacity retention rate of the all-solid-state lithium-ion battery. The present invention is used in the field of lithium-ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of all-solid-state lithium-ion battery polymer electrolyte interface modification, and specifically relates to a method for modifying the interface of an all-solid-state lithium-ion battery by utilizing two-dimensional titanium carbide-acetylene black. Background Art

[0002] In recent years, due to the depletion of fossil energy, people have begun to devote themselves to the development and utilization of new energy such as solar energy, wind energy, and tidal energy. Therefore, lithium-ion batteries that can store electricity efficiently have emerged. They have the advantages of high energy density, high operating voltage, and low self-discharge rate, and are widely used in actual production and life. However, the endless occurrence of electric vehicle fires also reveals that liquid lithium-ion batteries are prone to fire or explosion caused by leakage and thermal runaway, which limits their further popularization and application.

[0003] Solid-state lithium-ion batteries can perfectly solve the above problems, but the poor interface contact and low room temperature ionic conductivity of solid-state lithium-ion batteries have always troubled people. In addition, lithium-ion batteries generally have the risk of lithium dendrites piercing the diaphragm during the cycle, causing the battery to short-circuit and catch fire. Therefore, in the research process of all-solid-state lithium-ion batteries, good contact between polymer electrolytes and electrodes, uniform deposition of lithium ions on the positive electrode, formation of a stable solid electrolyte interface film and excellent room temperature conductivity are all key issues to be solved.

[0004] Solid-state lithium batteries have three main components: cathode, anode and solid electrolyte. During discharge, lithium ions and electrons migrate in opposite directions, accompanied by cathode reduction and anode oxidation. The electrolyte interface in solid-state lithium-ion batteries involves the following reaction steps: (i) lithium ion diffusion in the electrolyte, (ii) charge transfer process, (iii) lithium ion diffusion in the electrode, (iv) interfacial reaction, etc. A stable and intimate contact interface is required to ensure the smooth progress of the above reaction steps. In 2020, Chen et al. proposed a new strategy to improve the stability of the interface by forming an electrolyte buffer layer on the rough surface of the electrode and solid electrolyte to improve the stability of the interface (ACS Appl. Mater. Interfaces 2020, 12, 15120-15127). And a layer of graphite is coated on the side of the electrolyte facing the lithium anode to connect the electrode / solid electrolyte. This structure greatly improves the interface stability and reduces the interfacial impedance of the solid-state battery. The graphite buffer layer has a significant enhancement effect on the interfacial contact and an inhibitory effect on lithium dendrites. The assembled solid-state battery showed good rate performance at 1C, 2C and 4C, and this electrode / electrolyte design method showed good application prospects in solid-state lithium batteries. In addition to solid electrolyte modification, cathode surface modification is also another effective method to mitigate interfacial degradation. Yang et al. synthesized a continuous and compact lithium aluminum titanium phosphate (LATP) coating on the surface of lithium cobalt oxide by low-temperature treatment (J. Power Sour. 2018, 3, 388, 65–70). The solid-state lithium-ion battery assembled with PEO-based polymer electrolyte and LATP-modified lithium cobalt oxide showed high capacity retention at 4.2V (93.2% after 50 cycles), indicating that the modified coating can effectively enhance the cycle stability of PEO-based polymer electrolyte. A stable interface is crucial to the electrochemical performance of solid-state lithium-ion batteries. Most studies have focused on modifying the lithium cathode to suppress lithium dendrites. It can be seen that controlling the interfacial stability of the electrode / electrolyte is very important to improve the electrochemical performance of the battery. Summary of the invention

[0005] The present invention solves the problem of poor and unstable interface modification of polymer electrolytes in the prior art, and proposes a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black. Compared with the original polymer electrolyte membrane, the modified polymer electrolyte membrane has greater ionic conductivity, smaller impedance and lower activation energy, which is manifested in the full combination of the positive electrode and the surface of the polymer electrolyte membrane when the half-cell is assembled for circulation, and the formation of a stable and rapid SEI film. The modified polymer electrolyte membrane prepared by this method can improve the charge / discharge specific capacity and cycle stability of the corresponding all-solid-state lithium-ion battery.

[0006] The object of the present invention can be achieved by the following method: a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide (MXene) and acetylene black, characterized in that the specific steps are: mixing the two-dimensional titanium carbide and acetylene black evenly, adding a polymer electrolyte precursor solution, adjusting the concentration to an appropriate concentration with an organic solvent and stirring evenly, preparing a modified coating on the surface of the polymer electrolyte by a scraping method, and drying in an oven to obtain a polymer electrolyte with a two-dimensional titanium carbide-acetylene black modified interface layer;

[0007] The mass ratio of the two-dimensional titanium carbide and acetylene black is 1-4:1-4. Since both have excellent electrical conductivity, the modified interface layer can have dual-carrier characteristics of ion conduction and electron conduction under the premise of ion conduction of the polymer electrolyte, so that the electric lines are evenly distributed, and the excessive lithium ions in the local area are eliminated, so that they are evenly deposited on the surface of the negative electrode. During charging, if there is no polarization of the negative electrode, the current density distribution at different positions on the surface of the negative electrode mainly depends on the distance between them and the positive electrode. The current density is large at places close to the positive electrode, and the current density is small at places far from the positive electrode. This current density distribution is called the initial current distribution. However, due to the existence of polarization of the interface layer, when the current passes through the electrode, it is equivalent to an equivalent resistor in series between the electrode-electrolyte interface, and its value is equivalent to the polarization degree. The current density passing through the negative electrode close to the positive electrode is large, the negative electrode polarization value is also large, and the voltage drop caused by polarization is also large, so that the actual current density at various locations on the entire negative electrode surface tends to be uniform, thereby obtaining a uniform lithium deposition layer. Therefore, improving the polarization degree of the negative electrode can improve the uniform deposition ability;

[0008] The mass ratio of the two-dimensional titanium carbide and acetylene black mixed solid to the polymer electrolyte precursor liquid is 1-5:5, and a polymer electrolyte with a mixed conductive layer is prepared. When other conditions are determined, if the conductivity of the electrolyte is large, that is, the conductivity is strong, the difference in solution voltage between the positive electrode and the negative electrode is small, and it can be relatively easy to adjust by polarizing the negative electrode so that the current density is evenly distributed on the positive electrode; if the polarization degree of the electrolyte is very small, or even close to zero, then increasing the conductivity of the electroplating solution is unlikely to improve the uniform deposition ability and deep deposition ability much, so it is necessary not only to have an electrolyte with good conductivity but also to have a modified layer with a large polarization effect to form a polymer electrolyte with a mixed conductive layer;

[0009] The organic solvent for adjusting the concentration includes one or more of N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide, and an effective solvent for preparing a polymer electrolyte precursor solution is obtained;

[0010] The invention also defines a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black, characterized in that the organic solvent is dripped at a rate of 20 drops / min to prevent the drug from hanging on the wall and causing the polymer electrolyte precursor solution to be uneven, and the stirring time is 8-14 hours. The dripping speed and stirring are one of the key factors for obtaining a uniform modified coating. The two are combined with the polymer electrolyte and the modified coating to prepare a uniform modified coating, so that the lithium ion deposition current density is uniform, lithium dendrites are eliminated, and a spherical lithium metal deposition layer is generated, which will not puncture the diaphragm, thereby ensuring the safety and longevity of the lithium-ion solid-state battery.

[0011] Further defined, the method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black is characterized in that the thickness of the modified coating is 10-50 μm, which can ensure the uniformity and flatness of the modified layer, form a good polarization resistance, balance the current density, and make lithium ions deposit evenly to form a spherical lithium ion deposition morphology;

[0012] The vacuum drying temperature of the polymer electrolyte is 100-120°C, which is higher than the boiling point of the solvent and much lower than the decomposition temperature of the electrolyte, so that the solvent in the polymer electrolyte is completely evaporated to become an all-solid electrolyte, and micropores are formed during evaporation to form lithium ion transmission channels, thereby improving the conductivity of the all-solid polymer electrolyte and ensuring the stability of the polymer electrolyte.

[0013] The invention also provides that the method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black is characterized in that the two-dimensional titanium carbide is obtained by etching titanium aluminum carbide (Ti3AlC2) with hydrofluoric acid. During the reaction, the hydrofluoric acid first reacts with the aluminum oxide on the surface and then reacts with the metal aluminum. The metal aluminum can be dissolved in the hydrofluoric acid to generate [AlF6] 3- , thereby etching the aluminum in the titanium aluminum carbide to form a two-dimensional titanium carbide with an accordion structure.

[0014] The hydrofluoric acid is prepared from lithium fluoride and hydrochloric acid, and the preparation process of this method will improve the safety of the experiment;

[0015] The etched two-dimensional titanium carbide is collected after washing with distilled water and centrifugation. In the experiment, the etched aluminum, i.e. the generated soluble [AlF6] 3- After washing, a pure two-dimensional titanium carbide with an organ structure is obtained, which allows electrons to be evenly distributed on its surface while lithium ions can smoothly pass through the organ gaps, increasing the conductivity of the electrolyte.

[0016] It is also defined that the method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black is characterized in that when the modified polymer electrolyte is assembled into a battery, the modified interface is in contact with the lithium sheet, and the two-dimensional titanium carbide and acetylene black that conduct electrons in the modified layer are combined to be equivalent to an equivalent resistor in series between the electrode-electrolyte interface, which promotes uniform distribution of electrons. The value is equivalent to the polarization degree, and the current density passing through the negative electrode that is close to the positive electrode is large, the negative electrode polarization value is also large, and the voltage drop caused by polarization is also large, so that the actual current density at various locations on the entire negative electrode surface tends to be uniform, thereby obtaining a uniform lithium deposition layer. Therefore, improving the polarization degree of the negative electrode can improve the uniform deposition ability, make the current density of lithium ion deposition the same, induce uniform deposition of lithium ions, and inhibit the generation of lithium dendrites. On the other hand, the combined addition of two-dimensional titanium carbide and acetylene black can promote the dense and efficient formation of the solid electrolyte interface (SEI) film. Due to the inherent fluorine terminals in the two-dimensional titanium carbide, it can react with lithium ions during the initial lithiation process and form a solid electrolyte interface film containing lithium fluoride in situ between the polymer electrolyte and the lithium anode interface. Due to the effect of lithium fluoride, the metallic lithium on the two-dimensional titanium carbide tends to grow horizontally, showing a smooth surface and a dense structure, significantly inhibiting the formation of lithium dendrites, and tending to form spherical lithium deposits, solving the problems of unstable solid electrolyte interface film and large interface impedance.

[0017] Compared with the existing technology, the present invention effectively reduces the bulk impedance and interface impedance of the polymer electrolyte, forms a stable and dense solid electrolyte interface film between the polymer electrolyte and the lithium positive electrode, prevents the formation of lithium dendrites that affect the battery cycle performance and safety performance, and improves the charge / discharge specific capacity and capacity retention rate of the all-solid-state lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the modified results of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments;

[0019] Figure 1 is the bulk impedance diagram of the comparative film of the present invention;

[0020] Figure 2 The bulk impedance diagram of a membrane using a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0021] Figure 3 is a curve showing the change of conductivity of the comparative membrane of the present invention with temperature;

[0022] Figure 4 The conductivity curve of the membrane using two-dimensional titanium carbide-acetylene black to modify the interface of all-solid-state lithium-ion batteries varies with temperature;

[0023] Figure 5It is the specific capacity-efficiency diagram of the comparative example of the present invention;

[0024] Figure 6 The specific capacity-efficiency diagram of a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black;

[0025] Figure 7 It is a capacity-voltage diagram of a comparative example of the present invention;

[0026] Figure 8 The capacity-voltage diagram of a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black;

[0027] Fig. 9 It is a magnification diagram of the comparative example of the present invention;

[0028] Fig.10 A rate diagram of a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black;

[0029] Fig.11 The impedance diagram of the symmetrical battery of the comparative example of the present invention after being placed for a certain number of days;

[0030] Fig.12 The impedance diagram of a symmetrical battery placed for days using a method of modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0031] Fig.13 is a curve showing the change of interface impedance with temperature in the comparative example of the present invention;

[0032] Fig.14 This is a curve showing the change of interface impedance with temperature for a method of modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0033] Fig.15 It is a constant current polarization diagram of a comparative example of the present invention;

[0034] Fig.16 This is a constant current polarization diagram of a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black;

[0035] Fig.17 This is a SEM image of the lithium sheet surface after the lithium iron phosphate half-cell of the comparative example of the present invention has been cycled 50 times;

[0036] Fig.18 This is a SEM image of the lithium sheet surface after 50 cycles of a lithium iron phosphate half-cell using a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0037] Fig.19 This is a SEM image of the lithium sheet surface of the lithium iron phosphate half-cell of the comparative example of the present invention after being left at 40° C. for 10 hours;

[0038] Fig. 20 This is a SEM image of the lithium sheet surface of a lithium iron phosphate half-cell after standing at 40°C for 10 hours using a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0039] Fig.21 This is the N1s graph of XPS of the modified layer of the comparative example of the present invention;

[0040] Fig. 22 This is the N1s graph of the modified layer XPS of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black;

[0041] Fig.23 This is the F1s graph of the XPS of the modified layer of the comparative example of the present invention;

[0042] Fig.24 This is the F1s graph of the modified layer XPS of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. DETAILED DESCRIPTION

[0043] The above contents of the present invention are further described in detail below through embodiments, but the subject matter of the present invention is not limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0044] Experimental drugs

[0045]

[0046] Experimental equipment

[0047]

[0048] Comparative Example 1

[0049] Weigh 0.1g of acetylene black solid powder in a weighing bottle and mix it evenly with the polymer electrolyte precursor slurry at a mass ratio of 2:5, and add N-methylpyrrolidone to adjust to an appropriate concentration. Apply it on the surface of the polymer electrolyte film with a thickness of 50μm, and place it in an oven to dry at 100℃. Assemble the prepared polymer electrolyte into a lithium iron phosphate half-cell.

[0050] Example 1

[0051] Weigh two-dimensional titanium carbide and acetylene black powder in a mass ratio of 1:1 in a weighing bottle, add polymer electrolyte precursor solution and NMP and mix evenly. Prepare a two-dimensional titanium carbide modified layer on the surface of the polymer electrolyte by blade coating. Assemble the prepared polymer electrolyte into a lithium iron phosphate half-cell.

[0052] The mass ratio of the solid powder to the polymer electrolyte precursor solution in the modified layer slurry, as well as the coating and drying methods of the modified polymer electrolyte are exactly the same as those in Comparative Example 1.

[0053] The above examples and comparative examples were characterized

[0054] 1) Impedance measurement. The resistance of polymer electrolyte is an important criterion for measuring the performance of polymer electrolyte, and has an important influence on the charge and discharge performance of the battery. Electrochemical AC impedance spectroscopy was used to test the resistance of polymer electrolyte. The instrument model was Shanghai Chenhua's CHI760E electrochemical workstation with a frequency of 0.01-100000 Hz. The polymer electrolyte was dried before the test, and stainless steel sheets (SS) were used as inert electrodes to assemble a stainless steel symmetrical blocking cell for testing.

[0055] 2) Charge and discharge test. Through the charge and discharge test of the battery, many important parameters of the battery in the cycle process are obtained, such as charge and discharge specific capacity, charge and discharge efficiency, voltage platform, etc. The instrument model is LAND battery test system CT2001A, the voltage is set to 2.6V-4.0V, the current rate is 0.5C, and the polymer electrolyte is assembled into a lithium iron phosphate half-cell for testing.

[0056] 3) Interface impedance test. Electrochemical impedance spectroscopy was used to test the interface impedance between the polymer electrolyte film and the electrode to determine the effect of the modified layer on the stability of the electrolyte-electrode interface. The electrochemical workstation model was CHI760E, with a frequency of 0.01-100000 Hz. Lithium iron phosphate half-cells were assembled and placed for different days for testing.

[0057] 4) Constant current polarization test. The interface stability between the polymer electrolyte and the electrode is tested by constant current polarization. The polymer battery is charged and discharged at a constant current density. The quality of the interface between the polymer electrolyte surface modification layer and the lithium electrode is determined by the voltage-time curve. The instrument model is LAND battery test system CT2001A, and the current density is 0.05 mA cm -2 The battery assembly method is lithium symmetrical battery.

[0058] 5) Scanning electron microscope (SEM) test. The surface morphology of the lithium sheet was observed by scanning electron microscope (SEM), the instrument model was FEI sirion200, the acceleration voltage was 0.2-30kV, the resolution was 20kV, the prepared sample was dried, placed in liquid nitrogen for quenching, and the obtained sample was glued to a sample holder coated with conductive glue for testing.

[0059] 6) X-ray photoelectron spectroscopy (XPS) test. The XPS test analyzes the composition of the interface passivation layer (SEI) between the polymer electrolyte and the lithium electrode, and observes the composition changes of the solid electrolyte interface film produced under different polymer electrolytes and different cycle states and the chemical state of each element. The instrument model is Thermo Fisher ESCALAB Xi+, the test parameters are aluminum / magnesium target (hν=1486.6eV), high resolution pass energy is 30eV, step size is 0.05eV, C1s standard peak is 285eV, the half-cell is disassembled before the test, and the side of the polymer electrolyte in contact with the lithium sheet is used as the test surface. The experimental data are fitted by XPSPEAK41.

[0060] Figure 1 The impedance of the polymer electrolyte is about 35Ω.

[0061] Figure 2 This is a bulk impedance diagram of a membrane using a two-dimensional titanium carbide-acetylene black modification method for all-solid-state lithium-ion battery interfaces. The resistance of the polymer electrolyte modified by two-dimensional titanium carbide-acetylene black is about 10Ω. The results show that the interface layer of two-dimensional titanium carbide-acetylene black can make the surface of the polymer electrolyte smoother and the contact with the lithium positive electrode closer.

[0062] Figure 3 The conductivity curve of the comparative membrane of the present invention changes with temperature. It changes linearly above 105°C and satisfies the Arrhenius equation. a / RT) was calculated, the activation energy of the polymer electrolyte is 8.43 kJ·mol -1 .

[0063] Figure 4 This is a curve showing the conductivity of the membrane modified by two-dimensional titanium carbide-acetylene black on the interface of all-solid-state lithium-ion batteries as a function of temperature. It is nonlinear in the temperature range of 25-105°C and linear above 105°C. The activation energy of the polymer electrolyte modified by two-dimensional titanium carbide-acetylene black is calculated to be 6.90 kJ·mol -1 , indicating that the two-dimensional titanium carbide-acetylene black modified layer enhances the migration of lithium ions.

[0064] Figure 5 The specific capacity-efficiency diagram of the comparative example of the present invention. The initial discharge capacity of the polymer electrolyte at 0.2C and 0.5C is 100 mAh·g -1 After 50 cycles, it decays to 66 mAh g -1 , the capacity decays faster.

[0065] Figure 6The specific capacity-efficiency diagram of a method for modifying the interface of all-solid-state lithium-ion batteries using two-dimensional titanium carbide-acetylene black. The initial discharge specific capacity of the modified polymer electrolyte at 0.2C and 0.5C is 111.8 mAh g -1 After 50 cycles, it is still 99.5 mAh g -1 , the attenuation is small.

[0066] Figure 7 This is a capacity-voltage diagram of the comparative example of the present invention. From the first cycle of the polymer electrolyte to the end of the 50th cycle, the battery's charge-discharge platform becomes shorter and shorter, indicating that during the battery cycle, the redox reaction balance of the cathode and anode is destroyed, and the polarization phenomenon is serious.

[0067] Figure 8 This is a capacity-voltage diagram of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. In 50 cycles, there was no significant change in the charge-discharge platform, and the charge-discharge platform potential difference of the modified polymer electrolyte was 0.24V, which was 0.06V lower than the 0.3V of the original polymer electrolyte, indicating that the modified layer effectively suppressed the occurrence of polarization, significantly reducing the potential difference of the polymer electrolyte.

[0068] Fig. 9 The discharge capacity of the original polymer electrolyte lithium iron phosphate half-cell at 0.1C, 0.2C, 0.5C, 1C, and 0.2C rates is 117 mAh·g -1 、102mAh·g -1 、75mAh·g -1 、35mAh·g -1 and 102mAh g -1 .

[0069] Fig.10 This is a rate diagram of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. The discharge capacity of the polymer electrolyte modified by two-dimensional titanium carbide-acetylene black at the same rate is 147 mAh g -1 、142.1 mAh g -1 、126.4mAh·g -1 、106.8mAh·g -1 and 142.9mAh·g -1 , which significantly improves the cycle stability of the battery.

[0070] Fig.11 The impedance diagram of the symmetrical battery of the comparative example of the present invention after being placed for 1, 5 and 10 days. f) are 53.69Ω, 59.71Ω and 47.07Ω respectively.

[0071] Fig.12 The impedance diagram of a symmetrical battery placed for a day using a two-dimensional titanium carbide-acetylene black modification method for the interface of an all-solid-state lithium-ion battery. The membrane resistance (R f ) are 18.61Ω, 19.45Ω and 20.78Ω respectively, which are much smaller than those before modification of two-dimensional titanium carbide-acetylene black. This shows that the occurrence of interfacial side reactions is suppressed by the modified layer. Lithium ions are induced to deposit uniformly, which can effectively reduce the interfacial impedance and improve the interfacial stability.

[0072] Fig.13 The curve of the interface impedance of the comparative example of the present invention changing with temperature. According to the Arrhenius equation, the activation energy of the solid electrolyte interface film before modification is 67.77 kJ·mol -1 .

[0073] Fig.14 This is a curve of the interface impedance variation with temperature for a method of modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. As shown in the figure, the interface impedance decreases with increasing temperature, and there is no inflection point, indicating that the conductive behavior of the generated solid electrolyte interface film does not change with temperature. Combined with the Arrhenius equation, the activation energy of the modified solid electrolyte interface film is 9.32 kJ·mol -1 , the activation energy after modification is reduced, indicating that the presence of two-dimensional titanium carbide and acetylene black can more easily reduce the interfacial side reactions and form a stable SEI film.

[0074] Fig.15 This is a constant current polarization diagram of the comparative example of the present invention. The assembled symmetrical battery fluctuates with the cycle, and the polarization voltage is 0.18V.

[0075] Fig.16 This is a constant current polarization diagram of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. The symmetrical battery assembled with the modified polymer electrolyte remained stable during the 100h cycle, and the polarization voltage (0.04V) was also significantly lower than that of the control example. It is further confirmed that the two-dimensional titanium carbide-acetylene black coating can effectively reduce the interfacial impedance of the polymer electrolyte and reduce polarization, thereby improving the battery's cycle performance.

[0076] Fig.17This is a SEM image of the lithium sheet surface after 50 cycles of the lithium iron phosphate half-cell of the comparative example of the present invention. The growth of lithium dendrites is a key factor in measuring the effect of the modified coating on the modification of the polymer electrolyte and electrode interface. The characterization results of 50 cycles of the original polymer electrolyte lithium iron phosphate half-cell show that with the increase in the number of cycles, the dendrites on the lithium sheet surface do not increase significantly, but the dendrite growth is uneven.

[0077] Fig.18 This is a SEM image of the lithium sheet surface after 50 cycles of a lithium iron phosphate half-cell using a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. After 50 cycles of the polymer electrolyte lithium iron phosphate half-cell modified with two-dimensional titanium carbide-acetylene black, there are no large and protruding dendrites on the surface of the lithium sheet, and the dendrites are evenly distributed. This shows that lithium dendrites are still growing on the surface of the lithium sheet modified with two-dimensional titanium carbide-acetylene black. However, the dendrites are evenly distributed, flatter and denser, and will not puncture the film to cause a short circuit, which can solve the problem of lithium dendrite aggregation and growth in lithium-ion batteries. Fig.19 and Fig. 20 The SEM images of the lithium sheet surface of the original polymer electrolyte lithium iron phosphate half-cell and the polymer electrolyte lithium iron phosphate half-cell modified by two-dimensional titanium carbide-acetylene black after standing at 40°C for 10 hours. The lithium ion deposition of the lithium iron phosphate half-cell assembled by the original polymer electrolyte is uneven, and is distributed on the surface of the lithium sheet in a moss-like or dendritic shape. During the cycle, due to the tip effect, lithium ions tend to gather on the formed dendritic surface. With the increase in the amount of deposition, the lithium dendrites grow severely and easily puncture the film, causing safety problems. The SEI film on the lithium sheet surface of the lithium iron phosphate half-cell assembled by the polymer electrolyte modified by two-dimensional titanium carbide-acetylene black is evenly distributed and spherical. According to the research of Shi et al., these spherical solid electrolyte interface films are hollow structures, which will be captured by the spherical solid electrolyte interface films during the generation of lithium dendrites, and no lithium deposition will occur. Combined with the charge and discharge performance, it shows that the interface layer modified by two-dimensional titanium carbide-acetylene black can perfectly solve the growth problem of lithium dendrites and has good electrode / electrolyte interface compatibility.

[0078] Fig.21 This is the N1s graph of XPS of the modified layer of the comparative example of the present invention.

[0079] Fig. 22 This is a N1s graph of the modified layer XPS of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. Unlike the comparative example, a peak of lithium nitride (Li3N) was found in the solid electrolyte interface film formed after the two-dimensional titanium carbide-acetylene black modification. Lithium nitride is one of the fastest lithium ion conductors with an ion conductivity of 10 at room temperature. 3 ~10 4 S cm -1It can effectively improve the lithium ion transmission capacity of the solid electrolyte interface film and alleviate the lithium ion concentration gradient on the cathode surface.

[0080] Fig.23 This is the F1s graph of the XPS of the modified layer of the comparative example of the present invention;

[0081] Fig.24 This is an F1s image of the modified layer XPS of a method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black. The presence of two-dimensional titanium carbide can promote the formation of lithium fluoride, forming a dense and stable solid electrolyte interface film between the polymer electrolyte and the lithium anode interface. In the presence of lithium fluoride, metallic lithium tends to grow horizontally on the two-dimensional titanium carbide, promoting the deposition of spherical lithium, and ensuring the safety of the battery during the cycle process.

Claims

1. A method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black, characterized in that The specific steps of the method are: mixing two-dimensional titanium carbide and acetylene black evenly, adding a polymer electrolyte precursor solution, adding an organic solvent and stirring evenly, preparing a modified coating on the surface of the polymer electrolyte by a scraping method, and placing the polymer electrolyte in an oven for vacuum drying to obtain a polymer electrolyte with a two-dimensional titanium carbide and acetylene black modified interface layer; The mass ratio of the two-dimensional titanium carbide to acetylene black is 1-4:1-4; The mass ratio of the two-dimensional titanium carbide and acetylene black mixed solid to the polymer electrolyte precursor liquid is 1-5:5; The organic solvent is one or more of N-methylpyrrolidone, N,N-dimethylformamide or N,N-dimethylacetamide; the modified coating has a modified interface in contact with the lithium sheet when the battery is assembled.

2. The method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black according to claim 1, characterized in that: The organic solvent is added dropwise at a rate of 20 drops / min, and the stirring time is 8-14 hours.

3. The method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black according to claim 1, characterized in that: The modified coating has a thickness of 10-50 μm.

4. The method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black according to claim 1, characterized in that: The vacuum drying temperature is 100-120°C.

5. The method for modifying the interface of an all-solid-state lithium-ion battery using two-dimensional titanium carbide-acetylene black according to claim 1, characterized in that: The two-dimensional titanium carbide is obtained by etching titanium aluminum carbide with hydrofluoric acid, wherein the hydrofluoric acid is prepared from lithium fluoride and hydrochloric acid, and the etched two-dimensional titanium carbide is collected after washing with distilled water and centrifugation.